THE REGULATION POLICIES ON LEGAL AID NORMS FOR INDONESIAN NATIONAL POLICE AND THEIR FAMILY - Sugiharto, Sugiharto (jfpublisher, 2022)
The legal aid for Indonesian National Police and their family is not regulated in Indonesian Law No. 2/2002 concerning the Indonesian National Police, but only regulated in Indonesian Government Regulation No. 3/2003 concerning the implementation of technical institutional general courts for Indonesian National Police, Indonesian Government Regulation No. 42/2010 concerning the rights of Indonesian National Police and Indonesian Police Chief Regulation No. 2/2017 concerning the procedures for providing legal aid by Indonesian National Police. This research aims to examine the policies on legal aid norms for Indonesian National Police and their family in the future. The method in this research is a normative juridical method or normative legal research. The sources of legal materials used are primary legal materials, such as legislation, official records in making laws and judges' decisions. In addition, secondary legal materials are in the form of publications on law include textbooks, legal dictionaries, legal journals, and comments on court decisions. The researcher also used tertiary legal materials, such as dictionaries, encyclopedias, lexicon and others. Based on the result of this research, it is requires to formulate legal aid norms for the members of Indonesian National Police and their families in the future by adding one Article 26 A in Indonesian Law No. 2/2002 concerning Indonesian National Police.